Short-term functional outcomes of patients with acute intracerebral hemorrhage in the native and expatriate population - Akhtar, Naveed; Kate, Mahesh; Kamran, Saadat; Joseph, Sujatha; Morgan, Deborah; Uy, Ryan; Babu, Blessy; Shanti, Shobhna; Shuaib, Ashfaq (Frontiers in Neurology, 2024)
Objectives Functional outcomes in patients with intracerebral hemorrhage (ICH) have not been well characterized in the Middle East and North Africa Region. We report the 30 and 90-day clinical outcomes in the native and expatriate of Qatar with ICH. Methods We evaluated the Glasgow Coma Scale (GCS), NIHSS, and imaging in the Qatar Stroke Registry (2013–22). The outcome measures were a modified Rankin Scale (mRS) at 90 days and mortality at 30 and 90 days. Unfavorable outcome was defined as mRS of 4–6. We performed non-parametric ROC analyses to measure the concordance index (C-index) to assess the goodness-of-fit of ICH score for predicting 30 day and 90-day mortality and functional outcome. Results 1,660 patients (median age of 49 (41.5–58) years; male 83.1%, expatriates 77.5%) with ICH, including supratentorial deep in 65.2%, cortical in 16.2%, infratentorial 16% and primary intraventricular in 2.5% were studied. The median baseline ICH volume was 7.5 (3.2–15.8) ml. An unfavorable outcome was seen in 673 (40.5%) patients at 90 days. The unfavorable 90-day outcome (mRS 4–6) was 49.2% in the native population vs. 44.4% in Africans, 39.0% in South Asian, 35.3% in Far Eastern, and 7.7% in Caucasians, p < 0.001. Mortality at 30 days and 90 days was 10.4 and 15.1%. Increasing age [OR (95% CI), 1.02 (1.00–1.03)], lower GCS [0.77 (0.73–0.80)], prior use of antiplatelet medications [1.82 (1.19–2.08)], higher ICH volume [1.03 (1.02–1.04)], and presence of any intraventricular hemorrhage [1.57(1.19–2.08)], were associated with unfavorable outcome. Conclusion In this relatively younger ICH cohort more than 75% were expatriates. The ICH volume, 90-day unfavorable outcome and mortality was lower in the expatriates compared to the local Arab population, likely related to the younger age and smaller size of the hemorrhages. Prognostic scoring systems may have to be modified in this population to avoid early withdrawal of care.